Dirección estratégica y gestión contable en la Municipalidad Provincial De Ucayali, Contamana 2023 - Rios Paima, Diana Marita (2024)
The purpose of this study was to determine the relationship between strategic direction and accounting management in the Provincial Municipality of Ucayali, Contamana 2023. The research was carried out using a descriptive and correlational methodology, using a non-experimental design. Data were collected through questionnaires based on the Likert scale, administered to 100 employees who gave their consent. The results revealed that 29% of respondents rated strategic direction as fair, especially due to inconsistency in the facilitation of activities by infrastructure and work environments. Similarly, 28% considered accounting management to be regular, highlighting the occasional lack of analysis of the financial statements to adequately inform the manager about the institution's financial situation. Ultimately, a positive and significant correlation was determined between strategic direction and accounting management in the Municipality, evidenced by a correlation coefficient of 0.871, with a significance value of less than 0.05.